Stentless balloon angioplasty preserving growth in adolescent congenital focal abdominal aortic coarctation: a case report - Siping Peng; Tao Hu (Journal of Cardiothoracic Surgery)
Abstract Background Congenital focal abdominal aortic coarctation (CAAC) is a rare vascular malformation frequently misdiagnosed as mid-aortic syndrome (MAS). A significant challenge in managing CAAC, particularly in young individuals, is addressing the coarctation while accommodating ongoing vascular growth and development. This case highlights the value of multidisciplinary collaboration and imaging-guided stentless balloon angioplasty in preserving vascular growth potential. Case presentation A 14-year-old male presented with a two-year history of refractory hypertension (peak:190/110mmHg) and exertional dizziness. Thoracoabdominal computed tomography angiography (CTA) revealed a focal coarctation (minimum luminal diameter: 4.2 mm, representing 70% stenosis) extending from the celiac artery origin to the superior mesenteric artery origin, without significant collateralization. Digital subtraction angiography (DSA)-guided balloon angioplasty (10 × 40 mm) resulted in a significant reduction of the transcoarctation pressure gradient from 45mmHg to 8mmHg, achieving normotension (120/80mmHg). At six-month follow-up, a 161% increase in aortic luminal diameter (to 11 mm) was observed, accompanied by complete regression of left ventricular hypertrophy (LVH), as evidenced by a decrease in interventricular septal thickness from 12 mm to 9 mm. Conclusions Stentless balloon angioplasty is an effective strategy in treating CAAC in adolescents, achieving both immediate hemodynamic relief and facilitating growth-adaptive aortic remodeling. Comprehensive aortic imaging is crucial for the diagnosis and management of refractory hypertension in adolescents.